Determination of the thermal properties of reinforced concrete coatings and methods for optimizing energy-efficient elements - Kalibekova Жадыра (Рroblems of engineering and professional education, 2023)
In the article we discussed reinforced concrete roofs and roof layers in multistorey residential buildings and considered the problem of improving the design of existing traditional heaters using modern thermotechnical requirements. Depending on the heater, it is shown how to use the heaters.